PERILAKU HIDUP BERSIH DAN SEHAT DI SEKOLAH DASAR NEGERI 004 DESA SUNGAI JALAU KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Gusmarlinda, Rizka; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Healthy living is a matter that should indeed be applied by everyone, considering the health benefits are very important for every human being, from the concentration in the move and work in everyday life would require health. For the realization of necessary health coaching clean and healthy life behavior with applied from as early as possible, so that the coaching and guidance easily applied continuously for survival, growth and development of physical, mental, and social individuals or groups in society. This study aims to investigate the implementation of nine indicators Clean and Healthy Behavior and social supervision of clean and healthy lifestyle. Research conducted at the State Primary School 004 Desa Sungai Jalau Kecamatan Kampar Utara KabupatenKampar. The population in this study were all in the implementation of the State Primary School which used 004 subjects in the study. And a sampling technique is to cluster sampling with total sample of 58 people. Analysis of the data in this study is quantitative descriptive. The results showed that educators have been active in the implementation and supervision of Clean and Healthy Behavior on schools and pupils. The level of knowledge the students in knowing and applying the Clean and Healthy Behavior is already high. The majority of students have had the awareness to implement the implementation of Clean and Healthy Behavior and adhere to social supervision applied cadres in schools.Keywords: Behavior Clean, Behavior Healthy, Analysis Quantitative